2011
DOI: 10.2147/jmdh.s17773
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and multidisciplinary approaches to dementia care

Abstract: Dementia is a clinical syndrome of widespread progressive deterioration of cognitive abilities and normal daily functioning. These cognitive and behavioral impairments pose considerable challenges to individuals with dementia, along with their family members and caregivers. Four primary dementia classifications have been defined according to clinical and research criteria: 1) Alzheimer’s disease; 2) vascular dementias; 3) frontotemporal dementias; and 4) dementia with Lewy bodies/Parkinson’s disease dementia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(77 citation statements)
references
References 167 publications
0
67
0
3
Order By: Relevance
“…In Hellström and Torres' (2013) study, most participants wanted to know and learn about the condition in order to be prepared for the future, whilst other studies, including the present one, revealed that couples where one partner (McRae, 2010;Hellström & Torres, 2016). In the literature, learning about dementia seems to be perceived as either helpful, or depressing and limiting, by couples where one partner has a diagnosis of dementia (Robinson et al 2015;Grand et al 2011;Hellström & Torres, 2016McRae, 2010). …”
Section: Meaningful Activities and Relationshipsmentioning
confidence: 70%
See 1 more Smart Citation
“…In Hellström and Torres' (2013) study, most participants wanted to know and learn about the condition in order to be prepared for the future, whilst other studies, including the present one, revealed that couples where one partner (McRae, 2010;Hellström & Torres, 2016). In the literature, learning about dementia seems to be perceived as either helpful, or depressing and limiting, by couples where one partner has a diagnosis of dementia (Robinson et al 2015;Grand et al 2011;Hellström & Torres, 2016McRae, 2010). …”
Section: Meaningful Activities and Relationshipsmentioning
confidence: 70%
“…Söderhamn et al 2014Clare et al 2008Leung et al 2015;Toms et al 2015;Keyes et al 2016 Planning ahead for future impact of the condition with the aim of increased sense of control. Robinson et al 2015;Grand et al 2011;SCIE, 2015; Alzheimer's Association; Hellström & Torres, 2016 Adapting activity to capability Adapting capability to activity (and goals of activities), in order to feel that activities are manageable and successful. Genoe & Dupuis, 2014, McGovern, 2015Groat and Weems, 2009;McRae, 2010 Doing things together Everyday chores and activities are meaningful and an important source of pleasure and opportunity to do things together.…”
Section: Methodsmentioning
confidence: 99%
“…That is, declines in general health or increased frailty may be a harbinger of cognitive deterioration. Likewise, in a recent dementia review (Grand et al, 2011), it was argued that until the precise underlying mechanisms are known, attention should be placed on the maintenance of general health. Although the issue of mechanism(s) of cognitive decline remains important, recent theorizing underscores the importance of improving the general health of those at greatest risk and suggests that such a focus may be as beneficial as targeting specific etiologic mechanisms (Dartigues and Feart, 2011; Song et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…За прикажување на карактеристичните промени кои се појавуваат кај лицата со АБ со развојот на болеста употребена е поделбата на Utton (2009, р.380) Користејќи ги описите на Grand et al (2011) за нарушувањата кои се појавуваат кај лицата со АБ ќе биде разгледана следната поделбата на нарушувањата: Grand et al (2011) истакнуваат дека деменцијата и АБ често предизвикуваат неподвижност, опадната физичка кондиција, загуба на тонус на мускул, слаба координација и сл. Авторите понатаму се согласуваат дека овие појави го доведуваат лицето во поголема опасност од паѓање и повреда.…”
Section: нарушувања предизвикани од аб кои влијаат врз односот со опкunclassified
“…Според Grand et al (2011) во когнитивни нарушувања спаѓаат: ослабнување на меморијата, неспособност за координирање на движењата, неможноста да се идентификуваат специфични објекти од средината, потешкотиите во фокусирањето и распределбата на вниманието, талкање, дефицити во активностите на секојдневниот живот, визуо-просторна дисфункција и други когнитивни нарушувања кои не се од интерес за ова истражување. Како што истакнуваат Silverberg et al (2011), развојот на АБ најчесто започнува со ослабнување на сеќавањето, но подоцна ги засегнува сите когнитивни функции.…”
Section: ) когнитивни нарушувањаunclassified